Factors-5

From Homeworkwiki

Jump to: navigation, search

Factorize :

(i) 2 x 2 - 7 x + 6

(ii) 3 x 2 - 11 x - 4

(iii) 6 + 11 x + 3 x 2

(iv) 7 - 12 x - 4 x 2

Solution :

(i) 2 x 2 - 7 x + 6 = 2 x 2 - 4 x - 3 x + 6 [since, - 4 - 3 = - 7 and, ( - 4 ) X ( - 3 ) = 12]

= 2 x (x - 2) - 3 (x - 2)

= (x - 2) (2x - 3)

(ii) 3 x 2 - 11 x - 4 = 3 x 2 - 12 x + x - 4

= 3 x (x - 4) + 1 (x - 4)

= (x - 4) (3 x + 1)

(iii) 6 + 11 x + 3 x 2 = 6 + 9 x + 2 x + 3 x 2

= 3 (2 + 3 x) + x (2 + 3x)

= (2 + 3x)(3 + x)

(iv) 7 - 12 x - 4 x 2

= 7 - 14 x + 2 x - 4 x 2

= 7 (1 - 2 x) + 2 x (1 - 2 x)

= (1 - 2 x) (7 + 2 x)

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams